Kraus' recreation and leisure in modern society - Hurd, Amy R.; Anderson, Denise M. 1970-; Mainieri, Tracy
"Kraus' Recreation and Leisure in Modern Society provides a detailed introduction to the history, developments, and current trends in leisure studies"--Provided by publisher.